Pelatihan Guru dalam Implementasi Pendidikan Inklusif di Madrasah Ibtidaiyyah AT- Tarbiyah dan At Thohiriyah - Anisah, Ani Siti; Ade Holis; Asep Tutun Usman; Jafar Amirudin; Sopa Siti Marwah; Iis Komariah (Universitas Garut, 2025)
This community service program aimed to enhance teachers' understanding and skills in implementing inclusive education at Madrasah Ibtidaiyah Al-Thahiriyah and At-Tarbiyah, particularly in addressing the needs of students with learning difficulties such as slow learners. Many elementary schools and madrasahs have yet to apply differentiated instructional strategies effectively due to limited teacher training and awareness. Therefore, this program involved 30 teachers and was designed to provide both theoretical knowledge and practical experience in inclusive education through training sessions, workshops, and hands-on classroom mentoring. The evaluation employed both quantitative and qualitative methods, including pre-tests, post-tests, classroom observations, teacher reflections, and student interviews. Results indicated that the majority of participants were highly satisfied with the training, demonstrated increased understanding and teaching competence, and felt more confident in applying inclusive teaching practices. Furthermore, the program had a positive impact on school management and contributed to creating a more adaptive and supportive learning environment. Although some teachers still faced challenges in implementing the strategies, the program was generally regarded as effective and relevant to the needs of the madrasahs. It is expected that similar initiatives can be replicated and expanded to promote equitable, inclusive, and quality education across Indonesia.